Multi-Variate Analyses of Coral Mortality From the 2014–2015 Stony Coral Tissue Loss Disease Outbreak Off Miami-Dade County, Florida - Spadafore, Rachele; Fura, Ryan; Precht, William F.; Vollmer, Steven V. (Frontiers in Marine Science, 2021)
Environmental compliance monitoring associated with the Port Miami dredging project (2013–2015), designed to assess the impact of project-generated sediments on the local coral community, fortuitously captured a thermal bleaching event and the first reports of an emergent, highly contagious, white-plague-like coral disease outbreak in the fall of 2014. The disease, now termed stony coral tissue loss disease (SCTLD), has decimated reefs throughout Florida and is now spreading across the Caribbean. The high prevalence of disease, the number of affected species, and the high mortality of corals affected suggests SCTLD may be the most lethal coral disease ever recorded. Previous analyses of the dredge monitoring data have reached mixed conclusions about the relative impact of dredging on coral mortality and has often parsed out disease susceptible individuals to isolate the impacts of dredging only. We use multi-variate analyses, including time-based survival analyses, to examine the timing and impacts of dredging, coral bleaching, and disease on local coral mortality. By examining the status of corals monthly from the October 2013 to July 2015 observational period, we found that coral mortality was not significantly affected by a coral’s proximity to the dredge site or sediment burial. Instead, coral mortality was most strongly impacted by disease and the emergence of SCTLD during the monitoring period. During the 2-year monitoring period, 26.3% of the monitored corals died, but the only conditions significantly affected by the dredge were partial burial and partial mortality. The strongest link to mortality was due to disease, which impacted coral species differently depending on their susceptibility to SCTLD. The focus on disturbances associated with dredging created a circumstance where the greater impacts of this emergent disease were downplayed, leading to a false narrative of the resulting mortality on the local coral communities. The results of this study reveal that while local events such as a dredging project do have quantifiable effects and can be harmful to corals, regional and global threats that result in mass coral mortality such as thermal stress and disease represent an existential threat to coral reefs and must be urgently addressed.